Investigating the impact resistance of E-glass/ Polyester composite materials in variable fiber-to-matrix weight ratio composition. Issue 1 (31st December 2023) - Asmare, Sisay; Yoseph, Bisrat; Jamir, T. M.
Abstract: E-glass/polyester composite is formed by combining E-glass fiber as reinforcement with a polyester resin matrix. These constitute materials have different properties from the composite they built. The fiber mat with 65, 55, and 35 weight percentages and a matrix with weight percentages 35, 45, and 65 have been prepared. In each composition reinforcement, the test samples are modeled using Ansys ACP—pre and fabricated using the hand-layup technique. By setting three test samples for each class of composition, a total of nine test samples are prepared. Impact tests are conducted on each test sample using an Izod impact testing machine and using Ansys explicit dynamics numerically. The maximum mechanical properties are obtained in 65 by 35 fiber-to-matrix ratios of the composite experimentally and numerically when compared with the other stated composition. Results of the numerical analysis show that good mechanical properties can be achieved using balanced and compatible reinforcement with the matrix in the composite.